2017
DOI: 10.18632/oncotarget.18586
|View full text |Cite
|
Sign up to set email alerts
|

TLR4 interaction with LPS in glioma CD133+ cancer stem cells induces cell proliferation, resistance to chemotherapy and evasion from cytotoxic T lymphocyte-induced cytolysis

Abstract: Despite advances in treatment modalities, 5-year survival among glioma patients remains poor. Glioma cancer stem cells (CSCs) exhibit high tumorigenic activity and are associated with resistance to treatment and tumor recurrence. Because overexpression of toll-like receptor 4 (TLR4) correlated with cancer development, we investigated LPS-induced TLR4 signaling in glioma CD133-positive (CD133+) CSCs. The proliferation of CD133+ CSCs isolated from CSCs derived from the U251 and SF295 glioma cell lines and from h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 73 publications
2
28
0
Order By: Relevance
“…Among multiple LPS-induced cytokines in cancer cells are particularly important angiogenic factor VEGF-A [55,60,181], immunosuppressive TGF-beta [60,182], and a variety of chemokines recruiting BM-derived myeloid cells [34,178] that promote tumor progression through their own mechanisms. On a cellular level, TLR4 activation increases tumor cell proliferation [69,177,183], migration [64,175], invasion [159], and survival [58,176,184] that collectively results in resistance to therapy [58,61,69,136,183]. Some studies also reported increased stemness due to expansion of cancer stem cells [153,183].…”
Section: Direct Functional Effects Of Tlr4 On Tumor Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among multiple LPS-induced cytokines in cancer cells are particularly important angiogenic factor VEGF-A [55,60,181], immunosuppressive TGF-beta [60,182], and a variety of chemokines recruiting BM-derived myeloid cells [34,178] that promote tumor progression through their own mechanisms. On a cellular level, TLR4 activation increases tumor cell proliferation [69,177,183], migration [64,175], invasion [159], and survival [58,176,184] that collectively results in resistance to therapy [58,61,69,136,183]. Some studies also reported increased stemness due to expansion of cancer stem cells [153,183].…”
Section: Direct Functional Effects Of Tlr4 On Tumor Cellsmentioning
confidence: 99%
“…On a cellular level, TLR4 activation increases tumor cell proliferation [69,177,183], migration [64,175], invasion [159], and survival [58,176,184] that collectively results in resistance to therapy [58,61,69,136,183]. Some studies also reported increased stemness due to expansion of cancer stem cells [153,183]. Additional effects include induction of epithelial-mesenchymal transition (EMT) [66,180] and evasion of immunosurveillance [183], both of which might reflect TLR4activated macrophage properties enabling tissue repair and resilience against pathogen-produced toxins.…”
Section: Direct Functional Effects Of Tlr4 On Tumor Cellsmentioning
confidence: 99%
“…The presence of TLR4 has been previously described in GBM, particularly in CD133 + tumor stem cells [38,39], and also in GBM cell lineages A172, U87MG [3,40,41], and U251 [42]. Such TLR4 positivity conferred a proliferative phenotype to these tumor cells [38,42]. Furthermore, the presence of TLR2 was also detected in murine GL261 glioma cell line, and the activation of this receptor leads to an invasive and migratory profile of the tumor cells [43].…”
Section: Discussionmentioning
confidence: 76%
“…Moreover, an associated expression of these receptors were observed in GBM cases, suggesting their role in tumor aggressiveness. The presence of TLR4 has been previously described in GBM, particularly in CD133 + tumor stem cells [38,39], and also in GBM cell lineages A172, U87MG [3,40,41], and U251 [42]. Such TLR4 positivity conferred a proliferative phenotype to these tumor cells [38,42].…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation